Enhancing microalgal biomass harvesting efficiency using thermoresponsive polymers - Wang, Xuexue (My University, 2024)
Microalgae-based biorefining presents significant potential; however, the high costs associated with the harvesting of algal biomass pose substantial challenges to its commercialization. This research aims to develop innovative technology for algal cell harvesting, facilitating a cost-competitive and environmentally sustainable biorefinery. Poly(N-isopropylacrylamide) (PNIPAM), known for its temperature-induced phase transition properties, is explored as a means to capture algal cells within the cultivation medium. This study investigates PNIPAM and its derivatives to elucidate the fundamental principles and potential applications of thermoresponsive polymers (TRPs) for the harvesting of microalgae. Variants of PNIPAM were synthesized, and the impacts of charge, molecular weight, amine content, and polymer concentration on the phase transition temperature and degree of phase separation were systematically examined. Results indicated that the lower critical solution temperature (LCST) of PNIPAM decreases with increasing concentration, with the rate of decrease attenuating at higher molecular weights. Notably, amine content did not exert a significant influence on the LCST. The efficacy of these properties on the harvesting of Chlorella vulgaris was assessed, achieving a remarkable 92% algae harvesting efficiency (AHE) with PNIPAM (300 kDa). However, amine-modified TRPs did not enhance harvesting performance. These findings underscore the potential of TRPs as a viable polymer class for microalgae harvesting, thereby advancing the microalgae industry. To broaden the applicability of TRPs, additional algal strains with varying sizes, culture media, and cell wall compositions were evaluated. In addition to C. vulgaris, strains such as Chlorococcum oleofaciens, Chlorella protothecoides, and Nannochloropsis oculata were investigated. Results demonstrated that both higher molecular weight and concentration positively influenced cell harvesting efficacy. PNIPAM (300 kDa) consistently harvested over 90% of algal cells across all four strains within the cultivation medium. PNIPAM was found to be particularly effective for N. oculata, which thrives in seawater and possesses a cell size of 2-10 μm with a cell wall primarily composed of glucosamine. Notably, the introduction of amine-induced positive charge did not facilitate harvesting even when the charge-shielding effect is diminished. Structural transitions of TRPs following phase changes indicated that algal cells may become encapsulated within the polymer meshwork, facilitating their extraction. The harvesting process resulted in a vitality reduction of more than 50% in algal cells, alongside noticeable shrinkage and damage to the cell wall. Furthermore, the grafting of PNIPAM onto various substrate materials, including cotton fabric, polyester fabric, polyester sheets, and polystyrene flexible sheets, was explored to enhance the convenience and cost-effectiveness of PNIPAM recycling and reuse. Among the tested grafted PNIPAMs, PNIPAM (300 kDa) grafted onto cotton fabric exhibited the highest grafting yield (2.38 ± 0.39 mg/cm²) and optimal AHE of 72.31 ± 0.56%. Allowing the polymer to dissolve completely prior to heating significantly improved AHE during the harvesting process. Moreover, PNIPAM-grafted cotton fabrics demonstrated the capacity for reuse across more than 20 cycles before a decline in AHE was observed. The implementation of grafted PNIPAM on substrate materials presents a promising cost-effective strategy for algal harvesting, thereby promoting the commercialization of microalgae biorefineries. Overall, this study demonstrates the significant potential of PNIPAM as a novel approach for the efficient harvesting of microalgae, addressing key challenges in the commercialization of microalgae-based biorefineries. This research lays the groundwork for future developments in algae biorefining processes, encouraging further exploration and optimization of thermoresponsive polymers to foster a more cost-effective and environmentally friendly approach to microalgae harvesting and biorefinery commercialization.
Keywords: Bioenergy; Algae harvesting; Poly-(N-isopropylacrylamide); Phase transition; Lower critical solution temperature